Differences between match and training situations for water polo goalkeepers - Clément, J.; Croteau, F.; Oliveira, J. (Sports Engineering, 2022)
Background: Training volume can be estimated for players in team sports using inertial measurement units. Specific variables such as jumps and jump intensity have shown correlation with fatigue markers in players at the goalkeeper position. Therefore, the goal of this study was to explore the feasibility of analyzing training volume and intensity for water polo goalkeepers using IMU variables. Methods: Three senior national water polo team female goalkeepers were recruited for this study. Data from seven training sessions and seven international matches were recorded. Training volume was calculated and specific events were counted (jumps and kicks). Activity intensity score was calculated as a proportion of time spent in high-intensity activities. A paired t test was performed to compare training and match conditions. Results: The mean duration of training sessions was significantly shorter than matches (74.4 ± 14.4min vs 91.4 ± 5.4min, p < 0.01). The mean activity intensity score was also significantly lower in training sessions vs. matches (47.9 ± 3.5% vs 58.6 ± 3.8%, p = 0.04). Acceleration rate of change per minute was not different between training and matches (p = 0.10). Conclusion: This study showed the feasibility of using IMU to provide meaningful training and match metrics in a small sample of female water polo goalkeepers. This type of analysis can be used to describe both volume and intensity of training in future studies.